In Vitro Antibiofilm Efficacies of Different Antibiotic Combinations with Zinc Sulfate against Pseudomonas aeruginosa Recovered from Hospitalized Patients with Urinary Tract Infection - Walid Elkhatib; Ayman Noreddin (MDPI AG, 2014)
Urinary tract infections (UTIs) are a serious healthcare dilemma influencing millions of patients every year and represent the second most frequent type of body infection. Pseudomonas aeruginosa is a multidrug-resistant pathogen causing numerous chronic biofilm-associated infections including urinary tract, nosocomial, and medical devices-related infections. In the present study, the biofilm of P. aeruginosa CCIN34519, recovered from inpatients with UTIs, was established on polystyrene substratum and scanning electron microscopy (SEM) and was utilized for visualization of the biofilm. A previously described in vitro system for real-time monitoring of biofilm growth/inhibition was utilized to assess the antimicrobial effects of ciprofloxacin, levofloxacin, moxifloxacin, norfloxacin, ertapenem, ceftriaxone, gentamicin, and tobramycin as single antibiotics as well as in combinations with zinc sulfate (2.5 mM) against P. aeruginosa CCIN34519 biofilm. Meanwhile, minimum inhibitory concentrations (MICs) at 24 h and mutant prevention concentrations (MPCs) at 96 h were determined for the aforementioned antibiotics. The real-time monitoring data revealed diverse responses of P. aeruginosa CCIN34519 biofilm to the tested antibiotic-zinc sulfate combinations with potential synergisms in cases of fluoroquinolones (ciprofloxacin, levofloxacin, moxifloxacin, and norfloxacin) and carbapenem (ertapenem) as demonstrated by reduced MIC and MPC values. Conversely, considerable antagonisms were observed with cephalosporin (ceftriaxone) and aminoglycosides (gentamicin, and tobramycin) as shown by substantially increased MICs and MPCs values. Further deliberate in vivo investigations for the promising synergisms are required to evaluate their therapeutic potentials for treatment of UTIs caused by P. aeruginosa biofilms as well as for developing preventive strategies.